High-risk Pseudomonas aeruginosa clones harboring β-lactamases: 2024 update - Verónica Roxana Flores-Vega; Santiago Partida-Sanchez; Miguel A. Ares; Vianney Ortiz-Navarrete; Roberto Rosales-Reyes (Heliyon)
Carbapenem-resistant Pseudomonas aeruginosa is defined by the World Health Organization as a “high priority” in developing new antimicrobials. Indeed, the emergence and spread of multidrug-resistant (MDR) or extensively drug-resistant (XDR) bacteria increase the morbidity and mortality risk of infected patients. Genomic variants of P. aeruginosa that display phenotypes of MDR/XDR have been defined as high-risk global clones. In this mini-review, we describe some international high-risk clones that carry β-lactamase genes that can produce chronic colonization and increase infected patients' morbidity and mortality rates.